2022
DOI: 10.1021/acs.jafc.2c02512
|View full text |Cite
|
Sign up to set email alerts
|

Gypensapogenin I Suppresses Cell Proliferation in Triple-Negative Breast Cancer Via Triggering the Closure of AKT/GSK3β/β-Catenin and Notch-1 Signaling Pathways

Abstract: Jiaogulan (Gynostemma pentaphyllum) tea is a functional food that is commercially available worldwide. Gypensapogenin I (Gyp I), which is a natural damarane-type saponin, was obtained from the hydrolysates of total gypenosides. The present research was performed to investigate the potential antiproliferation effect of Gyp I in MDA-MB-231 cells and the underlying mechanisms. Here, we found that Gyp I attenuated survival, inhibited proliferation, and induced apoptosis in MDA-MB-231 cells. Target prediction by bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Eurochevalierine D (4) was deduced to hold the molecular formula C 29 H 38 N 2 O 7 through its HRESIMS data analysis. The 1 H, 13 C, and DEPT NMR data demonstrated that compound 4 shared an analogous planar structure with 3. The delicate distinction between them were the absence of the hydroxyl at C-8a′ (δ C 43.9) in 4, and the configuration of Δ 5 ′ (13 ′ ) in 4 was E rather than Z in 3, which can be inferred by the HMBC correlations from H-4a′ to C-8a′, from H-1′ to C-8a′, and from H 3 -12′ to C-8a′, and the 1 H− 1 H COSY interactions of H-1′/H-8a′/H-4a′/H-8′, along with the NOESY correlations of H 2 -6′/ H 2 -14′ and H-4a′/H 3 -15′.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Eurochevalierine D (4) was deduced to hold the molecular formula C 29 H 38 N 2 O 7 through its HRESIMS data analysis. The 1 H, 13 C, and DEPT NMR data demonstrated that compound 4 shared an analogous planar structure with 3. The delicate distinction between them were the absence of the hydroxyl at C-8a′ (δ C 43.9) in 4, and the configuration of Δ 5 ′ (13 ′ ) in 4 was E rather than Z in 3, which can be inferred by the HMBC correlations from H-4a′ to C-8a′, from H-1′ to C-8a′, and from H 3 -12′ to C-8a′, and the 1 H− 1 H COSY interactions of H-1′/H-8a′/H-4a′/H-8′, along with the NOESY correlations of H 2 -6′/ H 2 -14′ and H-4a′/H 3 -15′.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…KBr) v max 3421, 2925, 1743, 1662, 1384, and 1233 cm −1 ; 1 H and13 C NMR data, see TableS3; HRESIMS m/z 533.2607 [M + Na] + (calcd. for C 29 H 38 N 2 O 6 Na, 533.2628).…”
mentioning
confidence: 99%
“…NEK8 knockdown also induced a decrease in the level of Akt phosphorylation at Ser473, which induced β-catenin phosphorylation at Ser552 47 , 55 (Fig. 6 M).…”
Section: Discussionmentioning
confidence: 88%
“…A large number of studies have reported that gypenoside can induce morphological changes and apoptosis and inhibit the proliferation of various cancer cells, such as lung cancer ( Li et al, 2021 ; Qi et al, 2021 ), breast cancer ( Zu et al, 2021 ; Tan et al, 2022 ), and kidney cancer cells ( Liu et al, 2021 ). However, the effect of gypenoside on gastric cancer is unclear.…”
Section: Resultsmentioning
confidence: 99%